2022
DOI: 10.48550/arxiv.2204.05225
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ZH production in gluon fusion at NLO in QCD

Long Chen,
Joshua Davies,
Gudrun Heinrich
et al.

Abstract: We present fully differential next-to-leading order results for Higgs production in association with a Z boson in gluon fusion. Our two-loop virtual contributions are evaluated numerically using sector decomposition, including full top-quark mass effects, and supplemented at high p T by an analytic high-energy expansion to order (m 4 Z , m 4 H , m 32 t ). Using the expanded results we also present a study of the top-quark mass scheme uncertainty at large p T .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 56 publications
6
7
0
Order By: Relevance
“…For the inclusive cross section, we have found that the NLO QCD corrections are of the same size as the LO contribution, and they increase the cross section by a factor of about 2. Our findings are in accordance with independent results in the literature [28,29]. We have also studied the invariant-mass distribution of the gg → ZH channel at NLO, observing that the perturbative K-factor is not flat across the M ZH range, specifically in the region of threshold ZH production and in the very-high-energy tail (M ZH > 1 TeV).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…For the inclusive cross section, we have found that the NLO QCD corrections are of the same size as the LO contribution, and they increase the cross section by a factor of about 2. Our findings are in accordance with independent results in the literature [28,29]. We have also studied the invariant-mass distribution of the gg → ZH channel at NLO, observing that the perturbative K-factor is not flat across the M ZH range, specifically in the region of threshold ZH production and in the very-high-energy tail (M ZH > 1 TeV).…”
Section: Discussionsupporting
confidence: 92%
“…[28] (which is in accordance with Ref. [29]) and we have found an agreement at the level of the Monte Carlo error. Furthermore, when we consider the relative importance of the scale uncertainties, we observe very similar results to Ref.…”
Section: Inclusive Cross Sectionsupporting
confidence: 93%
See 3 more Smart Citations